OROL BO’YI MINTAQASIDA 1960-YILLARIDAN 2022- YILLGACHA BO’LGAN O’ZGARISHLAR HAMDA OLIB BORILAYOTGAN ISLOHOTLAR TAHLILI (Conference Zone, 2022)
This article discusses the negative and positive changes that have taken place in the Aral Sea region since the 1960 s and to date, as well as the analysis of the tasks set in our state programs to improve the living standards of the peoples living in the Aral Sea region.